In the Limelight: Photoreceptors in Cyanobacteria - Devaki Bhaya (American Society for Microbiology, 2016)
ABSTRACT Certain cyanobacteria look green if grown in red light and vice versa. This dramatic color change, called complementary chromatic adaptation (CCA), is caused by alterations of the major colored light-harvesting proteins. A major controller of CCA is the cyanobacteriochrome (CBCR) RcaE, a red-green reversible photoreceptor that triggers a complex signal transduction pathway. Now, a new study demonstrates that CCA is also modulated by DpxA, a CBCR that senses yellow and teal (greenish blue) light. DpxA acts to expand the range of wavelengths that can impact CCA, by fine-tuning the process. This dual control of CCA might positively impact the fitness of cells growing in the shade of competing algae or in a water column where light levels and spectral quality change gradually with depth. This discovery adds to the growing number of light-responsive phenomena controlled by multiple CBCRs. Furthermore, the diverse CBCRs which are exclusively found in cyanobacteria have significant biotechnological potential.